2015
DOI: 10.1111/jcmm.12553
|View full text |Cite
|
Sign up to set email alerts
|

Identification of C‐terminal Hsp70‐interacting protein as a mediator of tumour necrosis factor action in osteoblast differentiation by targeting osterix for degradation

Abstract: In patients with inflammatory arthritis, tumour necrosis factor (TNF)-α are overproduced in inflamed joints. This leads to local erosion of cartilage and bone, periarticular osteopenia, as well as osteoporosis. But less is known regarding the molecular mechanisms that mediate the effect of TNF-α on osteoblast function. The purpose of this study was to test that C terminus of Hsc70-interacting protein (CHIP) has a specific role in suppressing the osteogenic activity of osteoblasts under inflammatory conditions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…CHIP, another novel post-translational regulator of Osx, plays an important role in the regulation of Osx in protein levels in osteoblast precursor cells upon treatment with tumor necrosis factor-α (TNF-α). Unlike the previous description, CHIP mediates the inhibition of Osx by TNF-α in K55 and K386 ubiquitination sites of Osx ( Xie and Gu, 2015 ).…”
Section: Post-translational Modifications Are Important For Osx Activmentioning
confidence: 80%
“…CHIP, another novel post-translational regulator of Osx, plays an important role in the regulation of Osx in protein levels in osteoblast precursor cells upon treatment with tumor necrosis factor-α (TNF-α). Unlike the previous description, CHIP mediates the inhibition of Osx by TNF-α in K55 and K386 ubiquitination sites of Osx ( Xie and Gu, 2015 ).…”
Section: Post-translational Modifications Are Important For Osx Activmentioning
confidence: 80%
“…We found that PTGS1 expression is highly induced in response to TNFα treatment and that the inflammatory cytokine could inhibit osteogenesis and bone formation by downregulating two core transcription factors for osteogenic differentiation: RUNX2 and OSX [24, 25]. TNFα is the key stimulating factor for activating the classical NF-κB pathway; for this reason, we hypothesized that targeting the NF-κB pathway may be a novel mechanism through which PTGS1 regulates the osteogenic differentiation of MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α acts as anti-osteogenic by inhibiting differentiation, proliferation, and activities of osteoblast. It upregulates CHIP-ubiquitin ligase protein, which results in the degradation of osterix (pro-osteoblastic transcription factor) ( 48 ). TNF-α also inhibits expression of BMP-induced ‘special AT-rich sequence binding protein 2’ (SATB2), which is another pro-osteoblastic transcription factor, by triggering NF-κB binding to SATB2 promoter ( 49 ).…”
Section: Inflammatory Mediators and Osteoporosismentioning
confidence: 99%